2011
DOI: 10.1002/jmri.22671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gadoxetic acid‐enhanced dynamic imaging and diffusion‐weighted imaging for the preoperative evaluation of colorectal liver metastases

Abstract: EOB-MRI was more useful for the detection of colorectal liver metastases, while DWI was more useful for their characterization. The combination of EOB-MRI and DWI showed significantly higher accuracy and sensitivity for the preoperative detection of small colorectal liver metastases than DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 31 publications
0
38
0
1
Order By: Relevance
“…7), was noteworthy. Previous studies have suggested that the combination of DWI with hepatospecific contrast-enhanced sequences may improve our ability to detect colorectal liver metastases [13][14][15][16][17][18]. However, these data were obtained in small, heterogenous series.…”
Section: Discussionmentioning
confidence: 96%
“…7), was noteworthy. Previous studies have suggested that the combination of DWI with hepatospecific contrast-enhanced sequences may improve our ability to detect colorectal liver metastases [13][14][15][16][17][18]. However, these data were obtained in small, heterogenous series.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, gadoxetic acid (Gd-EOB-DTPA, Primovist®; Bayer Healthcare, Berlin, Germany), which is a hepatocyte-specific MR contrast agent, has received much attention as a promising contrast medium for the evaluation of liver metastases [16][17][18]. In addition, several studies have demonstrated that the combination of DWI and gadoxetic acid-enhanced MRI can improve the accuracy and sensitivity for the detection of liver metastasis, especially for small liver metastasis, as well as after preoperative chemotherapy [19][20][21][22][23]. However, to the best of our knowledge, there have been no large series studies regarding this issue or data on the diagnostic performance of MRI with gadoxetic acid for the detection of CRLM in patients with NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Even for the primary detection of liver metastases, comparable results for DWI-and CE-MRI were reported in recently published studies [25][26][27][28][29]. Nevertheless, they stated the need for contrast-enhanced MR-imaging, especially in cases of PETnegative liver lesions with restricted diffusion in DW-Imaging, who often turned out to be FNH in the histopathological workup [12,16].…”
Section: Discussionmentioning
confidence: 49%